2004
DOI: 10.1074/jbc.m405390200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of a Family 54 α-l-Arabinofuranosidase Reveals a Novel Carbohydrate-binding Module That Can Bind Arabinose

Abstract: As the first known structures of a glycoside hydrolase family 54 (GH54) enzyme, we determined the crystal structures of free and arabinose-complex forms of Aspergillus kawachii IFO4308 ␣-L-arabinofuranosidase (AkAbfB). AkAbfB comprises two domains: a catalytic domain and an arabinose-binding domain (ABD). The catalytic domain has a ␤-sandwich fold similar to those of clan-B glycoside hydrolases. ABD has a ␤-trefoil fold similar to that of carbohydrate-binding module (CBM) family 13. However, ABD shows a number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 53 publications
3
76
0
4
Order By: Relevance
“…␣-LArabinofuranosidase B (Abfb) from Aspergillus niger shares 98% sequence identity with Aspergillus kawachii IFO4308 AbfB, which has an experimentally determined structure (PDB code 1wd3) (30). A homology model was obtained from the SWISS-MODEL Repository based on 1wd3 (31).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…␣-LArabinofuranosidase B (Abfb) from Aspergillus niger shares 98% sequence identity with Aspergillus kawachii IFO4308 AbfB, which has an experimentally determined structure (PDB code 1wd3) (30). A homology model was obtained from the SWISS-MODEL Repository based on 1wd3 (31).…”
Section: Methodsmentioning
confidence: 99%
“…BglI differs from the other proteins in two major facets; it forms a dimer in solution and has a pair of large distal hydrophobic patch regions. The other proteins are known to be monomeric (investigated by x-ray crystallography (28,30), gel filtration chromatography (43)(44)(45), native polyacrylamide gel (46), and both analytical ultracentrifugation and gel filtration chromatography (47)) and, excepting BSA, presented similar patterns of small, random hydrophobic patching on their surface (Fig. 2C).…”
Section: Table 2 Qcm-d Measured Adsorption Parameters For Proteins Onmentioning
confidence: 96%
“…CBMs have now been described that bind to the major polysaccharides found in the plant cell wall (for review, see Boraston et al, 2004), while modules that recognize the side chains of these polymers, and the products released through their deconstruction, have also been identified (Notenboom et al, 2001;Miyanaga et al, 2004;Montanier et al, 2009b). In general, the ligand specificity of CBMs reflects the substrate cleaved by the cognate enzyme (discussed further below).…”
Section: Cbmsmentioning
confidence: 99%
“…4, shown in dark gray). 9,43) A search for structural similarity, using the DALI server, indicated that its closest structural neighbors are several non catalytic domains. In relation to the catalytic domains of GH enzymes, it exhibits a slight structural similarity to the clan GH B enzymes, including GH16 κ carrageenase 44) and GH7 cellobiohydrolase.…”
Section: Gh42: a Possible Link Between Retaining And Invert-mentioning
confidence: 99%
“…We have since solved two more GH families, and provided the first crystal structures within GH54 and GH94. 9,10) These four GH enzymes have potential bioindustrial uses, and these "fold representatives" contribute to protein engineering application of all enzymes within the same family. In this review, we focus on the relationships across the CAZy families as revealed by determination of these 3 D structures, and discuss possible protein evolution.…”
mentioning
confidence: 99%